Imbalance of γδT17/γδTreg cells in the pathogenesis of allergic asthma induced by ovalbumin - Yang,Xia (2018)
We aimed to explore the imbalance between the T helper 17 γδT cells (γδT17) and the regulatory γδT cells (γδTreg) in asthmatic mice. Male Balb/c mice were randomly divided into the normal control group and the asthmatic model group. The asthmatic model group mice were intraperitoneally injected with the mixture of ovalbumin (OVA)/Al(OH)3 and then activated by exposure of the animals to OVA atomization. Airway hyperresponsiveness (AHR) was determined by a non-invasive lung function machine. Hematoxylin and eosin and Alcian blue-periodic acid Schiff staining were done for histopathological analysis. Interleukin (IL)-17 and IL-35 levels in bronchoalveolar lavage fluid were detected by ELISA. The percentage of IL-17+ γδT cells and Foxp3+ γδT cells in spleen cells suspension were detected and the transcription levels of RORγt and Foxp3 in the lung tissue were determined. Compared with the normal control, the severity of airway inflammation and AHR were higher in the asthmatic mice. Furthermore, mice in the asthmatic group displayed significant increases of IL-17+ γδT cells, expression of IL-17A, and RORγt, whereas control mice displayed marked decreases of Foxp3+ γδT cells, expression of IL-35, and transcription factor Foxp3. In addition, the mRNA expression of RORγt was positively correlated with the percentage of IL-17+γδT cells, and the mRNA level of Foxp3 was positively correlated with the percentage of Foxp3+ γδT cells. The imbalance of γδT17/γδTreg in the asthmatic mice may contribute to the pathogenesis of OVA-induced asthma.